EFFECT OF POLYMERS AND METAL IONS ON THE BEHAVIOR OF PITCH FROM A SPRUCE TMP-BASED SPECIALITY PAPER MILL BASED ON DSC AND CONFOCAL LSM ANALYSIS - Zhongguo Dai; George Court; Zhiqing Li; Yonghao Ni (BioResources, 2011)
The appropriate pitch control is critical in many pulp and paper operations. One of the important approaches for pitch control is to use synthetic polymers. In this paper, we provide evidence from differential scanning calorimetry (DSC) analysis that the pitch deposits formed with polymers, such as polyDADMAC and CPAM, had better thermal stability than those without these polymers. Metal cations also affected the thermal stability of deposited pitch, depending on their valencies. The confocal laser scanning microscope (CLSM) was used to determine the distribution of pitch in the handsheets, and the results showed that polymers can aggregate pitch particles, which facilitates the retention of pitch on the paper sheet.